APPLICATION OF SOME GROWTH REGULATORS IN THE INITATION AND DIFFERENTIATION OF CALLUS TO REGENERATION OF DWARF MARIGOLD (Tagetes patula cv. Nana) plants 1- CALLUS INITATION - Kasim Mahmoud Al-Hamdani (Mesopotamia Journal of Agriculture)
The current study applied many of growth regulators involved: 6-benzyladenine (BA) alone and interacted with the two auxin each of ; naphthalene acetic acid (NAA) and 2,4-dichlorophenoxyacetic acid (2,4-D). The callus was obtained from different explants (leaves, stem, and roots).The results showed that leaves were the best explants for callus initiation specially by application of BA with 2,4-D in solidified MS medium which gave 100% initiation percentage of callus in all interaction was used ,this interaction of BA and 2,4-D also was active in initiation of stem callus (85%) . The interaction of BA with NAA also gave higher initiation percentage of leaves and roots callus with height weight of leaves callus reached 9.847g/explants after 30 days of growth on MS medium supplemented with 5mgL-1 of BA and 0.1mgL-1of NAA. BA alone by the used concentrations was able to induce the callus in all explants , and showed 100% initiation percentage of leaves and roots callus at 4 and 5 mgL-1 concentrations and prompt ,on MS medium with5 mgL-1 BA, the growth of stem and roots callus reached to 4.78 and 3.87gm respectively after 30 days of culture .